A review of the importance of prognostic factors influencing the decision on bilateral removal of ovaries during hysterectomy performed for non-oncological reasons - Olejek, Anita; Cieślak-Steć, Małgorzata; Waksmański, Bogdan (Menopause Review/Przegląd Menopauzalny, 2008)
Hysterectomy is the most frequent non-obstetrical surgical procedure performed in women of reproductive and perimenopausal age. The decision to remove or leave the ovaries during hysterectomy is still a very controversial problem. The decision on extension operation is made easy in the case of coexisting pathology of the ovaries. Considering the range of the gynaecological operation requires an appreciation not only of the medical aspect, but also quality of life after the intervention and the wish of the patient. The paper discusses numerous prognostic factors having essential significance for the decision regarding simultaneous removal of the adnexa. Also discussed are downsides of premature surgical castration connected with removal of the adnexa during hysterectomy due to benign lesions